Clean environment - "Jones,Sara" (Wayland, Hove, 1993)
The book "Environment" by Sara Jones, published in 1993 as part of the "Human Rights" series. This 48-page hardcover examines various aspects of environmental degradation and the initiatives aimed at reform. It emphasizes the fragility of our planet and encourages readers to form their own perspectives on human rights related to the environment. The book is illustrated with both color and black-and-white photographs to complement the informative text.